2022
DOI: 10.3748/wjg.v28.i6.608
|View full text |Cite
|
Sign up to set email alerts
|

Is precision medicine for colorectal liver metastases still a utopia? New perspectives by modern biomarkers, radiomics, and artificial intelligence

Abstract: The management of patients with liver metastases from colorectal cancer is still debated. Several therapeutic options and treatment strategies are available for an extremely heterogeneous clinical scenario. Adequate prediction of patients’ outcomes and of the effectiveness of chemotherapy and loco-regional treatments are crucial to reach a precision medicine approach. This has been an unmet need for a long time, but recent studies have opened new perspectives. New morphological biomarkers have been identified.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 112 publications
(109 reference statements)
0
11
0
Order By: Relevance
“…Despite the evolving technologies in imaging diagnosis and the support of Artificial Intelligence in Hepatobiliary and Pancreatic Surgery (HPB) [ 5 , 11 , 12 , 13 , 14 ], the diagnosis of HCC with BDTT is very challenging. Its treatment is still debated due to a complex pre- and postoperative patients’ management [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the evolving technologies in imaging diagnosis and the support of Artificial Intelligence in Hepatobiliary and Pancreatic Surgery (HPB) [ 5 , 11 , 12 , 13 , 14 ], the diagnosis of HCC with BDTT is very challenging. Its treatment is still debated due to a complex pre- and postoperative patients’ management [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In cancer treatment, tumor morphology is considered a biomarker. While it is a useful biomarker, it is not a robust one since it is unable to predict the response to treatment in patients receiving systemic therapy [ 28 ]. Additionally, different morphological parameters have been reported by different studies, but none have been confirmed by all authors.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, morphological criteria (e.g., tumor size) can be modified by chemotherapy, and it is unclear which value should be taken into consideration (prior to or after treatment). Furthermore, tumor morphology provides only a snapshot of the tumor and does not reflect its evolution over time [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations